DDS Formulations Used in the Otolaryngology Field: Characteristics of Pharmacokinetics and Side Effects - Iwamoto, Takuya; Uebayashi, Rie; Kawase, Ryousuke (The Journal of Japan Society for Infection and Aerosol in Otorhinolaryngology, 2020)
The Drug Delivery System (DDS) technology has attracted much attention since the early 1970s. This technology enabled the development of novel drugs including sustained-release and prodrug preparations. DDS has been linked to improvement of drug efficacy and drug applicability to clinical practice. Understanding the pharmacokinetics and side effects of a drug is particularly critical in patient-tailored medicine. In this article, we described the characteristic pharmacokinetics and side effects of DDS drugs commonly used in the field of otolaryngology.